(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article explores the crucial role of suprasegmental features in spoken language. It defines key suprasegmental elements such as stress, intonation, rhythm, and pitch, emphasizing their functions in clarifying meaning, expressing emotions, structuring information, and facilitating crosslinguistic communication. The article highlights the importance of suprasegmentals in language acquisition, noting their impact on intelligibility and the challenges they pose for learners. Additionally, it underscores their relevance in speech technology and therapy, showcasing their practical applications. Ultimately, the article portrays suprasegmental features as integral to enriching communication, enhancing both linguistic expression and human connection